Influence of Brand Awareness, Brand Image, and Key Opinion Leaders on Hanasui Product Purchase Decisions - Ardiyanti, Vika Diyah; Fitriani, Itsna Rahma (JOBS (Jurnal Of Business Studies), 2024)
The skincare business in Indonesia is growing very rapidly. In the midst of intense competition for skincare products, skincare manufacturers are competing to offer products that suit consumers' needs and desires with various innovations and advantages. Apart from that, manufacturers are also aggressively promoting their products on social media using various methods to build brand awareness and brand image, which are very important assets because they can influence consumer perceptions and behavior. But currently, there is chaos in the world of skincare in Indonesia. Moreover, it is related to allegations that the ingredients in the product do not necessarily correspond to those listed and reported to BPOM. This problem has gone very viral since the appearance of a doctor known as the "Detective Doctor" who provides education based on laboratory tests of the ingredients in beauty products whether they match what is stated on the packaging or not (overclaim). Detective Doctors can also be considered Key Opinion Leaders (KOL). Key Opinion Leaders (KOL) can be said to be the same as influencers because they have the same influence on consumer behavior. This research aims to determine the influence of Brand Awareness, Brand Image, and Key Opinion Leaders on Hanasui Product Purchasing Decisions. This research is associative research and the type of data used is quantitative data. The population of this research is all the unknown number of Hanasui product users. The sample in this study consisted of 100 respondents. The technique used is multiple linear regression technique. The research results show that the Brand Awareness and Key Opinion Leader variables have a positive and significant effect on purchasing decisions for Hanasuni products. Meanwhile, Brand Image has a positive but not significant influence on the decision to purchase Hanasui products